Nanoparticles-Constructed Spinel Li4Ti5O12 with Extra Surface Lithium Storage Capability towards Advanced Lithium-ion Batteries. (1st September 2016) - Ge, Hao; Hao, Tingting; Zhang, Bing; Chen, Li; Cui, Luxia; Song, Xi-Ming
Graphical abstract: Abstract: Spinel Li4 Ti5 O12 (LTO) has been intensively investigated as promising anode material for large-scale stationary electrochemical storage of energy produced from renewable sources due to its remarkable structural stability and excellent safety. In this paper, nanoparticles-constructed LTO with extra surface lithium storage capability is successfully prepared in air at 600 °C via employing TiOSO4 ·2H2 O as Ti source. The newly prepared nanoparticles-constructed LTO displays enhanced electrochemical performances, demonstrating ultrahigh reversible capacity of 173 mAh g −1 at 0.5C and superior rate performance of more than 145 mAh g −1 at 30C between 1.0 and 2.5 V vs. Li + /Li. The influences of specific surface area and crystallinity on the extra surface lithium storage capability of the sintered samples for LIBs are investigated in detail in terms of reversible capacity, cyclability and rate capability. Our results reveal that not only specific surface area but also crystallinity and pored structure are vital for reducing electrode polarization and achieving extra surface lithium storage of LTO. We anticipate that the uniquely extra surface lithium storage reaction of LTO will get more attentions in the near future.